Directional characteristics of shallow water waves along southwestern Bay of Bengal. (15th July 2016) - Glejin, Johnson; Kumar, V. Sanil; Anoop, T.R.; Joseph, Jofia
Abstract: The aim of the present research is to investigate the directional characteristics of waves along the southwestern Bay of Bengal based on the measured data during 2010 at 14 m water depth. Diurnal, monthly and annual variation of reflected waves is studied for waves within a frequency range of 0.03–0.125 Hz to eliminate the influence of local wave growth processes. High values of directional width during the annual cycle over the southwestern Bay of Bengal is associated with the swell reflection from the coast during southwest monsoon season (June–September) and intrusion of moderate easterly winds propagating from Gulf of Thailand over the narrow land mass of Thailand and Myanmar. The reflected wave energy is maximum (14%) during the southwest monsoon due to the presence of long period and intermediate period waves and minimum (9%) during the northeast monsoon season (October–January). During fair-weather period (February–May), 10% of the total energy is propagated towards offshore. We also analyzed the relationship between directional and non-directional wave parameters using continuous wavelet transform and wavelet coherence analysis (WCA). WCA shown that reflection coefficient and total energy is directly/inversely proportional to the swells, when signal of period approximately less/greater than one day is observed. Highlights: Measured data by waverider buoy used to study directional characteristics. High values of directional width due to swell reflection and wind–sea. Sudden decrease in directional width during tropical cyclones. Percentage of reflected wave energy is maximum ( 14%) during SW monsoon.